Multicomponent nanoparticles as nonviral vectors for the treatment of Fabry disease by gene therapy - Ruiz de Garibay AP; Delgado D; del Pozo-Rodríguez A; Solinís MA; Gascón AR (Dove Medical Press, 2012)
Aritz Pérez Ruiz de Garibay, Diego Delgado, Ana del Pozo-Rodríguez, María Ángeles Solinís, Alicia Rodríguez GascónPharmacokinetics, Nanotechnology and Gene Therapy Group, Pharmacy Faculty, University of the Basque Country UPV/EHU, Vitoria-Gasteiz, SpainPurpose: Gene-mediated enzyme replacement is a reasonable and highly promising approach for the treatment of Fabry disease (FD). The objective of the present study was to demonstrate the potential applications of solid lipid nanoparticle (SLN)-based nonviral vectors for the treatment of FD.Methods: SLNs containing the pR-M10-αGal A plasmid that encodes the α-Galactosidase A (α-Gal A) enzyme were prepared and their in vitro transfection efficacy was studied in Hep G2 cells. We also studied the cellular uptake of the vectors and the intracellular disposition of the plasmid.Results: The enzymatic activity of the cells treated with the vectors increased significantly relative to the untreated cells, regardless of the formulation assayed. When the SLNs were prepared with protamine or dextran and protamine, the activity of the α-Gal A enzyme by the transfected Hep G2 cells increased up to 12-fold compared to that of untreated cells.Conclusion: With this work we have revealed in Hep G2 cells the ability of a multicomponent system based on SLNs to act as efficient nonviral vectors to potentially correct low α-Gal A activity levels in FD with gene therapy.Keywords: solid lipid nanoparticles, Fabry disease, nonviral vectors, gene therapy